Analysis of Empowerment of Human Resources (Member) in Improving Career Development (Case Study at PT. HNI-HPAI Bussines Center (BC9) Subdistrict Sudirejo 1) - Nur Fadhilah Sadly (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Empowerment which means an effort needed to build power, by encouraging, motivating, raising awareness of the potential that is owned and trying to develop the potential of a member (member). In running a multi-level marketing business, PT.HNI-HPAI cannot be separated from human resources (members). A member (member) will not run optimally without the support of a leader/mentor. The research approach used in this research is qualitative. Research locations are areas or places that will be used as research targets. This research was conducted at PT. Herbal Medicine Alwahida Indonesia (HPAI) Bussines Center 9. Jl. Clean Water, Ex. Sudirejo I Kec. Medan city of North Sumatra Province. Research time for this research was conducted from December 2019 to July. The strategy of the research that can be drawn 1) The upline's active role that nurtures the members can improve the quality and income of members every month. 2) Good communication between members (members) and the upline can increase the target of each member. 3) Fostering a sense of responsibility to all members by giving awards to members who are enthusiastic and motivated to always be active in their membership. And finally, there is a lot of training offered by the leadership / upline to members by holding training as interesting as possible to empower and manage members so that they are superior to members of competing companies. The results of the SWOT analysis that have been obtained in PT HNI-HPAI Business Center 9 Medan is The total score of each of the detailed factors, strength 3.25, weakness 0.15, opportunity 3.23, threat 0.18.